Autologous Fat Injection Laryngoplasty for Unilateral Vocal Fold Paralysis - Wen-Dien Chang (MDPI AG, 2021)
Background: Unilateral vocal palsy (UVFP) affects the voice and swallowing function and could be treated by various materials to achieve improved mucosal wave and better closure during phonation. Injection laryngoplasty is considered an exemplary method for these patients and could be injected as early as possible. We conducted a systematic review and meta-analysis for the subjective and objective outcomes of autologous fat injection laryngoplasty (AFIL) and assessed the effects for patients with UVFP. Methods: We searched studies from PubMed and EBSCO databases with PRISMA appraisal to search for articles about the effects of AFIL on UVFP. The published articles were reviewed according to our inclusion and exclusion criteria. The short- and long-term outcomes of perceptual, acoustic analysis, and quality of life were also analyzed by meta-analysis. Results: Eleven articles were reviewed, and seven studies were selected for meta-analysis. AFIL improves the perceptual outcome and some voice parameters in short-term and long-term results, i.e., jitter, shimmer, and maximal phonation time (MPT). It also significantly improved the voice handicap index (VHI) in the long term, suggesting an increase in quality of life. Conclusions: AFIL is considered a reliable treatment method for UVFP and could even last for over 12 months.